Integration of Religious Moderation Values in Islamic Education Curriculum: A Comparative Literature Study - Muhammad Habibi Setiawan; Siti Maryam (PT. Berkah Smart Academica, 2024)
This comparative literature study examines the integration of religious moderation values within Islamic education curricula. It explores the historical context, theoretical underpinnings, and practical applications of incorporating these values to counter extremism and promote social harmony. The study synthesizes existing literature from various geographical contexts, including Indonesia, Morocco, and Malaysia, to identify common themes, challenges, and best practices. The methodology involves a systematic review of academic articles, books, and policy documents related to Islamic education and religious moderation. The findings reveal that successful integration requires a multi-faceted approach, including curriculum reform, teacher training, and community engagement. The study highlights the importance of contextualizing moderation within local cultural and religious frameworks, while also addressing the challenges of countering extremist ideologies. The conclusion emphasizes the need for ongoing research and collaboration to foster educational environments that promote tolerance, inclusivity, and responsible citizenship. Key elements found include the necessity for incorporating critical pedagogy, promoting interfaith dialogue, and adapting to the challenges of globalization.